Alcoholic liver disease and exacerbation by malnutrition and infections: What animal models are currently available? - Bergheim, Ina; Eagon, Patricia K.; Dooley, Steven; Breitkopf-Heinlein, Katja (Annals of the New York Academy of Sciences, 2011)
Alcoholic liver disease remains a frequent and serious problem for increasing numbers of patients. Research has expanded our molecular understanding of the cellular basis of disease progression; however, translation into therapy is still hampered by a lack of suitable animal models for alcoholic liver disease, as well as from consequences of related liver damage due to malnutrition, hepatitis C virus infection, or abuse of other substances. Many patients with liver disease do not simply consume too much alcohol; they also suffer from comorbidities such as obesity or viral hepatitis, and/or may be addicted to other drugs besides alcohol. This review will summarize the currently available animal models to study liver disease due to either single causes or combinations of liver toxic substances/infections and alcohol.